Sarcopenia in pancreatic cancer – effects on surgical outcomes and chemotherapy - Chan, Miu Yee; Chok, Kenneth Siu Ho (World journal of gastrointestinal oncology, 2019)
Sarcopenia is found in up to 65% of pancreatic cancer patients. The definition and diagnostic methods for sarcopenia have changed over the years, and the measurement of skeletal muscle mass with cross-sectional imaging has become the most popular way of assessment, although the parameters measured vary among different studies. It is still debatable that there is an association between sarcopenia and postoperative pancreatic fistula, but most studies showed a higher risk in patients with sarcopenic obesity. Long-term survival is worse in sarcopenic patients, as shown by meta-analysis. Sarcopenia is also associated with decreased survival and higher toxicity in patients receiving chemotherapy, and chemotherapy also tends to potentiate sarcopenia. Treatment for sarcopenia still remains an area for research, although oral supplements, nutritional modifications and exercise training have been shown to improve sarcopenia.